Experimental Study and Simulation on the Seal Pressure of a Ferrofluid Seal Using Radial-Charged Magnets - Liu, Jiawei; Li, Decai; Zhang, Zhili (Frontiers in Materials, 2022)
As one of the most mature applications of ferrofluid, the pole shoes of a ferrofluid seal are easily damaged under the situation of the large radial beating of the main shaft. Meanwhile, due to the small size, the pole teeth commonly used in pole shoes harbor problems such as poor processability and low seal pressure under a large gap. In order to solve the aforementioned problems, we proposed a new structure of the ferrofluid seal that uses a radial-charged ring magnet as the magnetic source. Then, considering that the ring magnets have problems of uneven magnetization and installation difficulties, we used split magnets to take the place of ring magnets and proposed the second new structure. According to the study on the distribution of magnetic field in seal gap axially and circumferentially, we obtained the simulation results of the two new structures’ seal pressure. The results revealed that the new structure of the ferrofluid seal with rectangular magnets can solve the aforementioned problems and exhibited a certain amount of sealing pressure.